Transfer type photosensitive film, method for forming cured film pattern, cured film and touch panel

The transfer type photosensitive film with a tricyclodecane/tricyclodecene skeleton and acylphosphine oxide initiator, combined with a metal oxide layer, addresses corrosion and visibility issues in touch panels by forming a cured film pattern with low moisture permeability and improved adhesion, enhancing panel performance.

JP7614139B2Active Publication Date: 2025-01-15RESONAC CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2022089813
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-07
Publication Date
2025-01-15
Estimated Expiration
2037-03-28

AI Technical Summary

Technical Problem

Existing touch panels face issues with corrosion of metal wiring due to moisture ingress, increased electrical resistance, and visibility problems from electrode patterns, along with reduced screen transmittance and color differences due to optical reflection characteristics.

Method used

A transfer type photosensitive film using a photopolymerizable compound with a tricyclodecane or tricyclodecene skeleton and an acylphosphine oxide photopolymerization initiator, combined with a second resin layer containing metal oxide particles, to form a cured film pattern that suppresses steps and enhances adhesion and refractive index matching.

Benefits of technology

The solution effectively reduces moisture permeability, suppresses pattern visibility, and improves adhesion while maintaining high transmittance and reducing optical reflections, enhancing the overall performance of touch panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007614139000012
    Figure 0007614139000012
  • Figure 0007614139000013
    Figure 0007614139000013
  • Figure 0007614139000014
    Figure 0007614139000014
Patent Text Reader

Abstract

Provided are a transfer-type photosensitive film that can satisfactorily form a cured film pattern having sufficiently low moisture permeability while suppressing step differences on an electrode pattern, and a method for forming a cured film pattern and a touch panel using the same. [Solution] The transfer-type photosensitive film of the present invention comprises a support film and a first resin layer provided on the support film, and the first resin layer contains a photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton, and an acylphosphine oxide-based photopolymerization initiator.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transfer type photosensitive film, a method for forming a cured film pattern, a cured film, and a touch panel. [Background technology]

[0002] Liquid crystal display elements and touch panels (touch sensors) are used in large electronic devices such as personal computers and televisions, small electronic devices such as car navigation systems, mobile phones, smartphones and electronic dictionaries, and display devices for OA (Office Automation) and FA (Factory Automation) equipment.

[0003] Various types of touch panels have been put to practical use, but in recent years, the use of projected capacitive touch panels has been increasing. In general, in projected capacitive touch panels, in order to express two-dimensional coordinates using the X and Y axes, multiple X electrodes and multiple Y electrodes perpendicular to the X electrodes form a two-layer structure. ITO (Indium-Tin-Oxide) is the mainstream material for these electrodes.

[0004] Incidentally, since the frame region of a touch panel is an area where the touch position cannot be detected, narrowing the area of ​​the frame region is an important factor for improving the product value. Generally, metal wiring such as copper is formed in the frame region to transmit a detection signal of the touch position. When a touch panel is touched by a fingertip, corrosive components such as moisture or salt may invade the inside from the sensing region. If the corrosive components invade the inside of the touch panel, the metal wiring corrodes, and there is a risk of an increase in electrical resistance between the electrodes and the driving circuit or a break in the wiring.

[0005] In order to prevent corrosion of metal wiring, a method has been proposed in which a photosensitive resin composition layer containing a di(meth)acrylate compound having a dicyclopentanyl structure or a dicyclopentenyl structure is provided on a touch panel substrate, a predetermined portion of the photosensitive resin composition layer is cured by irradiation with active light, and then the remaining portion is removed to form a cured film of the photosensitive resin composition that covers a part or the whole of the substrate (see Patent Document 1 below). According to this method, a cured film having sufficiently low moisture permeability can be formed on the touch panel substrate.

[0006] On the other hand, projected capacitive touch panels have a problem of the so-called "bone-visible phenomenon" in which the transparent electrode pattern is reflected on the screen when modularized due to a large color difference caused by the difference in optical reflection characteristics between the part where the transparent electrode pattern is formed and the part where it is not formed. There is also a problem that the reflected light intensity increases between the substrate and the transparent electrode, or between the visibility improvement film (OCA: Optical Clear Adhesive) that bonds the cover glass and the transparent electrode pattern used in modularization and the transparent electrode pattern, reducing the transmittance of the screen.

[0007] In response to this, for example, Patent Document 2 listed below discloses a transparent conductive resin substrate that reduces the color difference between areas where the transparent electrode pattern is formed and areas where it is not formed by providing an index matching layer (optical adjustment layer) (hereinafter referred to as the "IM layer") between the base material and the transparent electrode pattern, thereby preventing the bone-seeming phenomenon and a decrease in the transmittance of the screen.

[0008] Furthermore, for example, Patent Document 3 listed below discloses a transfer film having adjacent first curable transparent resin layer with a low refractive index and a second curable transparent resin layer with a high refractive index, the refractive index of which is adjusted to a specific refractive index range, as a method for preventing a transparent electrode pattern from being visible. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2015-121929 A [Patent Document 2] Japanese Patent Application Publication No. 8-240800 [Patent Document 3] International Publication No. 2014 / 084112 Brochure Summary of the Invention [Problem to be solved by the invention]

[0010] The present inventors have studied a transfer type photosensitive film using a photosensitive resin composition containing a di(meth)acrylate compound having a dicyclopentanyl structure (hereinafter referred to as a tricyclodecane skeleton) or a dicyclopentenyl structure (hereinafter referred to as a tricyclodecene skeleton). In the course of studying the improvement of the low moisture permeability and adhesion of the cured film pattern formed by this transfer type photosensitive film, they have found that when a cured film is formed on a transparent electrode pattern, the electrode pattern may be more clearly visible (pattern visibility may occur) even if the transparent electrode pattern is provided on an IM layer.

[0011] The present inventors further investigated the cause of the pattern visibility and found that depressions (also called steps) occur on the surface of the cured film provided on the ITO electrode pattern, and these depressions can be visually recognized as the pattern visibility.

[0012] The present invention aims to provide a transfer type photosensitive film capable of satisfactorily forming a cured film pattern having sufficiently low moisture permeability while suppressing steps on an electrode pattern, and a method for forming a cured film pattern and a touch panel using the same. [Means for solving the problem]

[0013] In order to solve the above problems, the present inventors have investigated the cause of the generation of the step, and have confirmed that when a cured film is formed on an ITO electrode and an IM layer under the same conditions, the reaction rate of the photosensitive resin layer provided on the IM layer is smaller than that on the ITO electrode. Based on this, the present inventors have hypothesized that the cause of the generation of the dent is that 1) in the exposure process, the unreacted photopolymerizable compound migrates from a place with a low reaction rate of the photosensitive resin layer to a place with a high reaction rate, and 2) in the annealing process in which the photosensitive resin layer is heated after exposure and development, the unreacted photopolymerizable compound volatilizes and a difference in thermal contraction occurs between a place with a high reaction rate and a place with a low reaction rate. From the viewpoint of suppressing the above-mentioned 1) and 2), the present inventors have investigated the composition of the photosensitive resin layer using a step evaluation test having an exposure process with a difference in exposure amount and an annealing process, and have found that by using a combination of a specific photopolymerizable compound and a specific photopolymerization initiator, the reaction rate difference can be suppressed and the step can be reduced, and have completed the present invention. However, simply increasing the amount of photopolymerization initiator in order to reduce the amount of unreacted photopolymerizable compound may result in development residues, making it difficult to form a good cured film pattern.

[0014] The present invention provides a transfer-type photosensitive film comprising a support film and a first resin layer provided on the support film, the first resin layer containing a photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton, and an acylphosphine oxide-based photopolymerization initiator.

[0015] According to the transfer type photosensitive film of the present invention, by having the above-mentioned configuration, it is possible to satisfactorily form a cured film pattern on the transparent electrode pattern while suppressing steps. The cured film pattern can function as an anti-rust film for the electrode pattern.

[0016] The reason why the above-mentioned effects are obtained is believed to be that the use of an acylphosphine oxide-based photopolymerization initiator allows a sufficient polymerization reaction rate to be obtained even for a photopolymerizable compound with a large molecular weight, thereby suppressing the above-mentioned events 1) and 2).

[0017] Increasing the blending amount of the photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton is effective in reducing moisture permeability and improving adhesion of the cured film pattern, but tends to increase the step generated in the cured film pattern provided on the transparent electrode pattern. According to the present invention, by combining a photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton with an acylphosphine oxide-based photopolymerization initiator, it is possible to form a cured film pattern having a high level of low moisture permeability and high adhesion while suppressing the step.

[0018] The acylphosphine oxide photopolymerization initiator may contain 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide. In this case, a cured film pattern having low moisture permeability and excellent color tone (especially a color tone with low yellowness and close to neutral) can be formed.

[0019] The first resin layer may further contain an oxime ester photopolymerization initiator. By using an acylphosphine oxide photopolymerization initiator and an oxime ester photopolymerization initiator in combination, the moisture permeability of the formed cured film pattern can be further reduced.

[0020] The transfer type photosensitive film according to the present invention may further include a second resin layer containing metal oxide particles provided on the first resin layer.

[0021] According to the above-mentioned transfer type photosensitive film, a cured film pattern can be satisfactorily formed on an electrode pattern, which can suppress steps and the bone visibility phenomenon.

[0022] The present invention also provides a first method for forming a cured film pattern, comprising the steps of: laminating a first resin layer of the transfer-type photosensitive film according to the present invention onto a substrate having an electrode pattern such that the side of the substrate on which the electrode pattern is provided is in close contact with the first resin layer; and exposing a predetermined portion of the first resin layer on the substrate to light, and then removing portions other than the predetermined portion to form a cured film covering a part or all of the electrode pattern.

[0023] The present invention also provides a second method for forming a cured film pattern, comprising the steps of: laminating the second resin layer and the first resin layer of the transfer-type photosensitive film according to the present invention having the second resin layer on a substrate having an electrode pattern such that the side of the substrate on which the electrode pattern is provided is in close contact with the second resin layer; and exposing predetermined parts of the second resin layer and the first resin layer on the substrate to light, and then removing parts other than the predetermined parts to form a cured film pattern covering a part or all of the electrode pattern.

[0024] According to the first and second methods for forming a cured film pattern of the present invention, the cured film pattern can be well formed while suppressing the step on the electrode pattern. Also, according to the second method for forming a cured film pattern of the present invention, the cured film pattern can have a function of adjusting the refractive index.

[0025] The present invention also provides a cured film obtained by curing the first resin layer in the transfer type photosensitive film according to the present invention.

[0026] The present invention also provides a cured film obtained by curing only the first resin layer, or both the first resin layer and the second resin layer, of the transfer-type photosensitive film according to the present invention having a second resin layer.

[0027] The present invention also provides a touch panel having a cured film pattern consisting of a cured product of the first resin layer in the transfer type photosensitive film according to the present invention, or a cured product of the second resin layer and a cured product of the first resin layer in the transfer type photosensitive film according to the present invention having a second resin layer. Effect of the Invention

[0028] According to the present invention, it is possible to provide a transfer type photosensitive film capable of satisfactorily forming a cured film pattern while suppressing steps on an electrode pattern, and a method for forming a cured film pattern and a touch panel using the same. [Brief description of the drawings]

[0029] [Figure 1] 1 is a schematic cross-sectional view showing a transfer type photosensitive film according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing a laminate having a cured film pattern formed using a transfer type photosensitive film according to one embodiment of the present invention on a substrate having a transparent electrode pattern. [Diagram 3] 1 is a schematic top view showing a touch panel according to an embodiment of the present invention; [Figure 4] 1 is a schematic cross-sectional view for explaining a step evaluation method according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, the embodiment for carrying out the present invention will be described in detail, with reference to the drawings as the case may be. However, the present invention is not limited to the following embodiment. In this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid, and "(meth)acrylate" means acrylate or the corresponding methacrylate. "A or B" may include either A or B, or may include both.

[0031] In addition, the term "layer" in this specification includes a structure having a shape formed on the entire surface as well as a structure having a shape formed on a part of the surface when observed in a plan view. In addition, the term "process" in this specification includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended effect of the process is achieved. In addition, a numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0032] Furthermore, in this specification, the content of each component in the composition means the total amount of the multiple substances present in the composition when the composition contains multiple substances corresponding to each component, unless otherwise specified. Furthermore, unless otherwise specified, the exemplified materials may be used alone or in combination of two or more kinds.

[0033] In addition, in the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples.

[0034] <Transfer-type photosensitive film> The transfer type photosensitive film of this embodiment includes a support film and a first resin layer provided on the support film. The transfer type photosensitive film of this embodiment may be a transfer type photosensitive film further including a second resin layer containing metal oxide particles provided on the photosensitive resin layer. These transfer type photosensitive films may further include a protective film provided on the photosensitive resin layer or the second resin layer.

[0035] Fig. 1 is a schematic cross-sectional view showing a transfer type photosensitive film according to one embodiment of the present invention. The transfer type photosensitive film 1 shown in Fig. 1 includes a support film 10, a first resin layer 20 provided on the support film 10, a second resin layer 30 provided on the first resin layer 20, and a protective film 40 provided on the second resin layer 30.

[0036] By using the above-mentioned transfer type photosensitive film, it is possible to form a pattern of a cured film in a single operation, which has both the function of protecting the metal wiring in the frame of a touch panel or the transparent electrodes of the touch panel, and the function of making the transparent electrode pattern invisible or improving the visibility of the touch screen.

[0037] (Support film) A polymer film can be used as the support film 10. Examples of the material for the polymer film include polyethylene terephthalate, polycarbonate, polyethylene, polypropylene, polyethersulfone, and cycloolefin polymer.

[0038] From the viewpoints of ensuring coverage and suppressing a decrease in resolution when irradiating with active light through the support film 10, the thickness of the support film 10 is preferably 5 to 100 μm, more preferably 10 to 70 μm, even more preferably 15 to 40 μm, and particularly preferably 15 to 35 μm.

[0039] (First Resin Layer) The first resin layer 20 is preferably formed from a photosensitive resin composition containing a binder polymer (hereinafter also referred to as component (A)), a photopolymerizable compound (hereinafter also referred to as component (B)), and a photopolymerization initiator (hereinafter also referred to as component (C)).

[0040] <Binder polymer> As the component (A), it is preferable to use a polymer having a carboxyl group, from the viewpoint of enabling patterning by alkaline development.

[0041] The component (A) is preferably a copolymer containing structural units derived from (meth)acrylic acid and (meth)acrylic acid alkyl ester. The copolymer may contain other monomers copolymerizable with the (meth)acrylic acid and (meth)acrylic acid alkyl ester as structural units. Specific examples of other monomers include (meth)acrylic acid glycidyl ester, (meth)acrylic acid benzyl ester, styrene, and (meth)acrylic acid cyclohexyl ester.

[0042] Examples of the (meth)acrylic acid alkyl ester include (meth)acrylic acid methyl ester, (meth)acrylic acid ethyl ester, (meth)acrylic acid butyl ester, (meth)acrylic acid-2-ethylhexyl ester, and (meth)acrylic acid hydroxylethyl ester.

[0043] Among these, from the viewpoints of alkaline developability (particularly developability in an inorganic alkaline aqueous solution), patterning ability and transparency, (meth)acrylic acid, (meth)acrylic acid glycidyl ester, (meth)acrylic acid benzyl ester, styrene, (meth)acrylic acid methyl ester, (meth)acrylic acid ethyl ester, (meth)acrylic acid butyl ester, (meth)acrylic acid 2-ethylhexyl ester, (meth)acrylic acid cyclohexyl ester, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentanyloxy (meth)acrylate, phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexylmaleimide, hydroxyethyl (meth)acrylate and hydroxybutyl ester are particularly preferred. The binder polymer is preferably a binder polymer having a structural unit derived from at least one compound selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid glycidyl ester, (meth)acrylic acid benzyl ester, styrene, (meth)acrylic acid methyl ester, (meth)acrylic acid ethyl ester, (meth)acrylic acid butyl ester, (meth)acrylic acid 2-ethylhexyl ester, and (meth)acrylic acid cyclohexyl ester, and more preferably a binder polymer having a structural unit derived from at least one compound selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid alkyl ester, (meth)acrylic acid glycidyl ester, and (meth)acrylic acid cyclohexyl ester. The binder polymer may also be a binder polymer obtained by addition reaction of isocyanatoethyl (meth)acrylate or glycidyl (meth)acrylate with hydroxyethyl (meth)acrylate or hydroxybutyl (meth)acrylate of a copolymer containing at least hydroxyethyl (meth)acrylate or hydroxybutyl (meth)acrylate as the structural unit.

[0044] In this embodiment, from the viewpoint of reducing the moisture permeability of the cured film, a binder polymer containing a group having a branched structure and / or an alicyclic structure in the side chain, a group having an acidic group in the side chain, and a group having an ethylenically unsaturated group in the side chain can be used. The group having a branched structure and / or an alicyclic structure in the side chain can be introduced by a monomer containing a group having a branched structure in the side chain, or a monomer containing a group having an alicyclic structure in the side chain. The group having an acidic group in the side chain can be introduced by a monomer containing a group having an acidic group in the side chain.

[0045] Specific examples of monomers containing a group having a branched structure in the side chain include, for example, i-propyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, i-amyl (meth)acrylate, t-amyl (meth)acrylate, sec-iso-amyl (meth)acrylate, 2-octyl (meth)acrylate, 3-octyl (meth)acrylate, t-octyl (meth)acrylate, etc. Among these, i-propyl (meth)acrylate, i-butyl (meth)acrylate, and t-butyl methacrylate are preferred, and i-propyl methacrylate and t-butyl methacrylate are more preferred.

[0046] Specific examples of monomers containing a group having an alicyclic structure in the side chain include (meth)acrylates having an alicyclic hydrocarbon group having 5 to 20 carbon atoms. More specific examples include (bicyclo[2.2.1]heptyl-2)(meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 3-methyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-1-adamantyl (meth)acrylate, 3-ethyladamantyl (meth)acrylate, 3-methyl-5-ethyl-1-adamantyl (meth)acrylate, 3,5,8-triethyl-1-adamantyl (meth)acrylate, 3,5-dimethyl-8-ethyl-1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, 3-hydroxy-2-(meth)acrylate, 2 ... acrylate, octahydro-4,7-menthanoinden-5-yl (meth)acrylate, octahydro-4,7-menthanoinden-1-ylmethyl (meth)acrylate, 1-menthyl (meth)acrylate, dicyclopentanyl (meth)acrylate, 3-hydroxy-2,6,6-trimethyl-bicyclo[3.1.1]heptyl (meth)acrylate, 3,7,7-trimethyl-4-hydroxy-bicyclo[4.1.0]heptyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, fenchyl (meth)acrylate, 2,2,5-trimethylcyclohexyl (meth)acrylate, and cyclohexyl (meth)acrylate. Among these (meth)acrylic acid esters, cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, fenchyl (meth)acrylate, 1-menthyl (meth)acrylate, and dicyclopentanyl (meth)acrylate are preferred, and cyclohexyl (meth)acrylate, (nor)bornyl (meth)acrylate, isobornyl (meth)acrylate, and 2-adamantyl (meth)acrylate are particularly preferred.

[0047] By containing a group having a branched structure and / or an alicyclic structure in the side chain of component (A), good adhesion to the substrate, particularly to a substrate having an index matching layer, can be obtained. In addition, by containing a group having an alicyclic structure in the side chain, the moisture permeability of the cured film can be reduced.

[0048] Specific examples of monomers containing a group having an acidic group in the side chain can be appropriately selected from known monomers, and include, for example, (meth)acrylic acid, vinylbenzoic acid, maleic acid, maleic acid monoalkyl ester, fumaric acid, itaconic acid, crotonic acid, cinnamic acid, sorbic acid, α-cyanocinnamic acid, acrylic acid dimer, an addition reaction product of a monomer having a hydroxyl group and a cyclic acid anhydride, ω-carboxy-polycaprolactone mono(meth)acrylate, etc. These may be appropriately produced or commercially available products may be used.

[0049] When the component (A) contains a group having an acidic group on the side chain, patterning by alkaline development becomes possible.

[0050] The group having an ethylenically unsaturated group in the side chain is not particularly limited, and the ethylenically unsaturated group is preferably a (meth)acryloyl group. In addition, the link between the ethylenically unsaturated group and the monomer is not particularly limited as long as it is a divalent linking group such as an ester group, an amide group, or a carbamoyl group. The method of introducing an ethylenically unsaturated group into the side chain can be appropriately selected from known methods, and examples thereof include a method of adding a (meth)acrylate having an epoxy group to a group having an acidic group, a method of adding a (meth)acrylate having an isocyanate group to a group having a hydroxyl group, and a method of adding a (meth)acrylate having a hydroxyl group to a group having an isocyanate group. Among them, the method of adding a (meth)acrylate having an epoxy group to a repeating unit having an acidic group is preferable in terms of being the easiest to manufacture and being low cost.

[0051] By containing a group having an ethylenically unsaturated group in the side chain of component (A), good adhesion to the substrate, particularly to a substrate having an index matching layer, can be obtained. In addition, the moisture permeability of the cured film can be reduced.

[0052] Based on the total amount of monomers constituting the component (A), the ratio of monomers constituting a group having a branched structure and / or an alicyclic structure in the side chain is preferably 10 to 70 mol%, more preferably 15 to 65 mol%, and even more preferably 20 to 60 mol%. Based on the total amount of monomers constituting the component (A), the ratio of monomers constituting a group having an acidic group in the side chain is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 50 mol%. Based on the total amount of monomers constituting the component (A), the ratio of monomers constituting a group having an ethylenically unsaturated group in the side chain is preferably 5 to 70 mol%, more preferably 10 to 60 mol%, and even more preferably 20 to 50 mol%. By satisfying the above monomer ratio, it is possible to improve in a well-balanced manner the patterning property by alkali development, the lamination property to the substrate, and the good adhesion to the substrate which may have an index matching layer.

[0053] From the viewpoint of resolution, the weight average molecular weight of the (A) component is preferably 10,000 to 200,000, more preferably 15,000 to 150,000, even more preferably 30,000 to 150,000, particularly preferably 30,000 to 100,000, and extremely preferably 40,000 to 100,000. The weight average molecular weight can be measured by the gel permeation chromatography method described in the examples of this specification.

[0054] The acid value of the component (A) is preferably 75 mgKOH / g or more from the viewpoint of easily forming a cured film (cured film pattern) having a desired shape by alkaline development. In addition, from the viewpoint of achieving both easy control of the cured film shape and the rust prevention of the cured film, the acid value of the component (A) is preferably 75 to 200 mgKOH / g, more preferably 75 to 150 mgKOH / g, and even more preferably 75 to 120 mgKOH / g. The acid value can be measured by the method described in the examples of this specification.

[0055] The first resin layer 20 may further contain a binder polymer other than the above-mentioned (A) binder polymer.

[0056] <Photopolymerizable compound> Examples of the component (B) include compounds having a tricyclodecane skeleton or a tricyclodecene skeleton. From the viewpoint of inhibiting corrosion of metal wiring and transparent electrode patterns, the compound having a tricyclodecane skeleton or a tricyclodecene skeleton preferably contains a di(meth)acrylate compound represented by the following general formula (B-1).

[0057] [ka] [In general formula (B-1), R 1 and R 2 each independently represents a hydrogen atom or a methyl group, X represents a divalent group having a tricyclodecane skeleton or a tricyclodecene skeleton, R 3 and R 4 each independently represents an alkylene group having 1 to 4 carbon atoms, n and m each independently represent an integer of 0 to 2, and p and q each independently represent an integer of 0 or more and are selected so that p+q=0 to 10.

[0058] In the above general formula (B-1), R 3 and R 4is preferably an ethylene group or a propylene group, more preferably an ethylene group, and the propylene group may be either an n-isopropylene group or an isopropylene group.

[0059] According to the compound represented by the above general formula (B-1), the divalent group having a tricyclodecane skeleton or a tricyclodecene skeleton contained in X has a bulky structure, thereby realizing low moisture permeability of the cured film and improving corrosion inhibition of metal wiring and transparent electrodes. Here, the terms "tricyclodecane skeleton" and "tricyclodecene skeleton" in this specification respectively refer to the following structures (each of which has an arbitrary bond):

[0060] [ka]

[0061] As the compound having a tricyclodecane skeleton or a tricyclodecene skeleton, from the viewpoint of low moisture permeability of the obtained cured film pattern, a compound having a tricyclodecane skeleton such as tricyclodecane dimethanol di(meth)acrylate is preferable. These are available as DCP and A-DCP (both manufactured by Shin-Nakamura Chemical Co., Ltd.).

[0062] From the viewpoint of reducing moisture permeability and step difference, the ratio of the compound having a tricyclodecane skeleton or a tricyclodecene skeleton in component (B) is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 80 parts by mass or more, of 100 parts by mass of the total amount of the photopolymerizable compounds contained in the photosensitive resin composition.

[0063] As the photopolymerizable compound of component (B), a photopolymerizable compound having an ethylenically unsaturated group other than a compound having a tricyclodecane skeleton or a tricyclodecene skeleton can be used. Examples of the photopolymerizable compound having an ethylenically unsaturated group include a monofunctional vinyl monomer having one polymerizable ethylenically unsaturated group in the molecule, a bifunctional vinyl monomer having two polymerizable ethylenically unsaturated groups in the molecule, and a polyfunctional vinyl monomer having at least three polymerizable ethylenically unsaturated groups in the molecule.

[0064] The contents of the (A) and (B) components are preferably 35 to 85 parts by mass, more preferably 40 to 80 parts by mass, even more preferably 50 to 70 parts by mass, and particularly preferably 55 to 65 parts by mass, of component (A) relative to 100 parts by mass of the combined amount of component (A) and component (B).

[0065] From the viewpoint of reducing moisture permeability and improving adhesion of the cured film pattern, the compound having a tricyclodecane skeleton or a tricyclodecene skeleton is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and particularly preferably 25 parts by mass or more, relative to 100 parts by mass of the total amount of the (A) component and the (B) component. In this embodiment, by combining the compound having a tricyclodecane skeleton or a tricyclodecene skeleton blended in the above ratio with an acylphosphine oxide-based photopolymerization initiator described later as a photopolymerization initiator, a cured film pattern having a high level of low moisture permeability and high adhesion can be formed while suppressing steps.

[0066] <Photopolymerization initiator> As the component (C), an acylphosphine oxide-based photopolymerization initiator is used. As the component (C), a conventionally known photopolymerization initiator other than the acylphosphine oxide-based photopolymerization initiator can also be used in combination.

[0067] Examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-phosphinate. The acylphosphine oxide photopolymerization initiator is available as IRGACURE TPO, IRGACURE 819, and IRGACURE TPO-L (all of which are product names manufactured by BASF Ltd.). By using the acylphosphine oxide photopolymerization initiator, a sufficient polymerization reaction rate can be obtained in the photosensitive resin layer, and pattern visibility can be suppressed.

[0068] Examples of photopolymerization initiators other than the acylphosphine oxide-based photopolymerization initiator include oxime ester-based photopolymerization initiators. By using an acylphosphine oxide-based photopolymerization initiator and an oxime ester-based photopolymerization initiator in combination, the moisture permeability of the formed cured film pattern can be further reduced.

[0069] The oxime ester photopolymerization initiator is preferably a compound represented by the following general formula (1), a compound represented by the following general formula (2), or a compound represented by the following general formula (3).

[0070] [ka]

[0071] In formula (1), R 11 and R 12 R each independently represents an alkyl group having 1 to 12 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, a phenyl group, or a tolyl group, and is preferably an alkyl group having 1 to 8 carbon atoms, a cycloalkyl group having 4 to 6 carbon atoms, a phenyl group, or a tolyl group, more preferably an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 4 to 6 carbon atoms, a phenyl group, or a tolyl group, and further preferably a methyl group, a cyclopentyl group, a phenyl group, or a tolyl group. 13represents -H, -OH, -COOH, -O(CH2)OH, -O(CH2)2OH, -COO(CH2)OH or -COO(CH2)2OH, preferably -H, -O(CH2)OH, -O(CH2)2OH, -COO(CH2)OH or -COO(CH2)2OH, more preferably -H, -O(CH2)2OH or -COO(CH2)2OH.

[0072] [ka]

[0073] In equation (2), two R 14 R each independently represents an alkyl group having 1 to 6 carbon atoms, and is preferably a propyl group. 15 R represents NO2 or ArCO (wherein Ar represents an aryl group), and Ar is preferably a tolyl group. 16 and R 17 each independently represents an alkyl group having 1 to 12 carbon atoms, a phenyl group, or a tolyl group, and is preferably a methyl group, a phenyl group, or a tolyl group.

[0074] [ka]

[0075] In formula (3), R 18 R represents an alkyl group having 1 to 6 carbon atoms, and is preferably an ethyl group. 19 is an organic group having an acetal bond, and R 19 R is preferably a substituent corresponding to 20 and R 21 R each independently represents an alkyl group having 1 to 12 carbon atoms, a phenyl group, or a tolyl group, and is preferably a methyl group, a phenyl group, or a tolyl group, and more preferably a methyl group. 22 represents a hydrogen atom or an alkyl group.

[0076] The compound represented by the above general formula (1) is available as IRGACURE OXE 01 (product name, manufactured by BASF Ltd.).

[0077] The compound represented by the above general formula (2) is available as DFI-091 (product name, manufactured by Daito ChemiX Co., Ltd.).

[0078] The compound represented by the above general formula (3) is available as ADEKA Optomer N-1919 (product name, manufactured by ADEKA Corporation).

[0079] In view of excellent photosensitivity and resolution, the content of the (C) component, relative to 100 parts by mass of the combined amount of the (A) and (B) components, is preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, even more preferably 1 to 3 parts by mass, and particularly preferably 1 to 2 parts by mass.

[0080] From the viewpoint of exposure sensitivity, the ratio of the acylphosphine oxide photopolymerization initiator in the component (C) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the total amount of the photopolymerization initiator contained in the photosensitive resin composition.

[0081] In addition, when an acylphosphine oxide photopolymerization initiator and an oxime ester compound are used in combination, from the viewpoints of pattern appearance, reliability, color, and curability, the mass ratio of the acylphosphine oxide photopolymerization initiator to the oxime ester compound is preferably 8:1 to 0.5:1, and more preferably 4:1 to 2:1.

[0082] From the viewpoint of further improving the rust resistance of the cured film, the photosensitive resin composition according to the present embodiment preferably further contains at least one compound (hereinafter also referred to as component (D)) selected from the group consisting of a triazole compound having a mercapto group, a tetrazole compound having a mercapto group, a thiadiazole compound having a mercapto group, a triazole compound having an amino group, and a tetrazole compound having an amino group. An example of a triazole compound having a mercapto group is 3-mercapto-triazole (manufactured by Wako Pure Chemical Industries, Ltd., product name: 3MT). An example of a thiadiazole compound having a mercapto group is 2-amino-5-mercapto-1,3,4-thiadiazole (manufactured by Wako Pure Chemical Industries, Ltd., product name: ATT).

[0083] Examples of the triazole compound having an amino group include compounds in which an amino group is substituted on benzotriazole, 1H-benzotriazole-1-acetonitrile, benzotriazole-5-carboxylic acid, 1H-benzotriazole-1-methanol, carboxybenzotriazole, etc., and compounds in which an amino group is substituted on a triazole compound containing a mercapto group, such as 3-mercaptotriazole or 5-mercaptotriazole.

[0084] Examples of the tetrazole compound having an amino group include 5-amino-1H-tetrazole, 1-methyl-5-amino-tetrazole, 1-methyl-5-mercapto-1H-tetrazole, and 1-carboxymethyl-5-amino-tetrazole. These tetrazole compounds may be water-soluble salts thereof. Specific examples include alkali metal salts of 1-methyl-5-amino-tetrazole, such as sodium, potassium, and lithium.

[0085] When the photosensitive resin composition contains the (D) component, the content thereof is preferably 0.05 to 5.0 parts by mass, more preferably 0.1 to 2.0 parts by mass, even more preferably 0.2 to 1.0 part by mass, and particularly preferably 0.3 to 0.8 parts by mass, relative to 100 parts by mass of the combined amount of the (A) and (B) components.

[0086] The photosensitive resin composition forming the first resin layer according to this embodiment may contain, as other additives, about 0.01 to 20 parts by mass each of phosphate esters having an ethylenically unsaturated group, adhesion imparting agents such as silane coupling agents, rust inhibitors, leveling agents, plasticizers, fillers, defoamers, flame retardants, stabilizers, antioxidants, fragrances, thermal crosslinking agents, polymerization inhibitors, etc., relative to 100 parts by mass of the total amount of the (A) component and the (B) component. These may be used alone or in combination of two or more kinds.

[0087] The thickness of the first resin layer may be 1 to 15 μm, preferably 2 to 10 μm, more preferably 3 to 8 μm, further preferably 4 to 6 μm, and particularly preferably 5 to 6 μm. By having a thickness of 1 to 15 μm, defects during application are reduced and a film with excellent transparency can be formed. In addition, the thickness of the first resin layer after curing (i.e., the thickness of the cured film pattern) is also preferably within the above range.

[0088] (Second Resin Layer) The second resin layer 30 is a layer containing metal oxide particles. The second resin layer 30 can have a relatively higher refractive index than the first resin layer 20 by containing metal oxide particles. The second resin layer 30 preferably has a refractive index at 633 nm in the range of 1.40 to 1.90, more preferably 1.50 to 1.90, further preferably 1.53 to 1.85, and particularly preferably 1.55 to 1.75. In addition, when the second resin layer contains a curable component, the refractive index at 633 nm of the second resin layer after curing is also preferably within the above range.

[0089] If the refractive index of the second resin layer 30 at 633 nm is within the above range, when the cured film pattern is provided on a transparent electrode pattern such as ITO, the refractive index becomes the intermediate value between the refractive index of various members (for example, OCA that bonds the cover glass used for modularization and the transparent electrode pattern) used on the cured film pattern, and it is possible to reduce the color difference due to optical reflection between the part where the transparent electrode pattern such as ITO is formed and the part where it is not formed, and it is possible to prevent the bone appearance phenomenon. In addition, it is possible to reduce the reflected light intensity of the entire screen, and it is possible to suppress the decrease in transmittance on the screen.

[0090] The refractive index of the transparent electrode such as ITO is preferably 1.80 to 2.10, more preferably 1.85 to 2.05, and even more preferably 1.90 to 2.00, while the refractive index of the member such as OCA is preferably 1.45 to 1.55, more preferably 1.47 to 1.53, and even more preferably 1.48 to 1.51.

[0091] The second resin layer 30 has a minimum light transmittance of preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more in the wavelength range of 450 to 650 nm. In addition, when the second resin layer contains a curable component, it is preferable that the minimum light transmittance of the second resin layer after curing in the wavelength range of 450 to 650 nm is also within the above range.

[0092] The second resin layer 30 may contain the above-mentioned components (A), (B) and (C), and may further contain the above-mentioned component (D) as necessary. The second resin layer 30 does not necessarily need to contain photopolymerizable components such as components (B) and (C), and the second resin layer may be photocured by utilizing a photopolymerizable component that migrates from an adjacent resin layer upon layer formation.

[0093] The second resin layer 30 contains metal oxide particles (hereinafter, also referred to as component (E)). As the metal oxide particles, it is preferable that the metal oxide particles contain metal oxide particles having a refractive index of 1.50 or more at a wavelength of 633 nm. This makes it possible to improve the transparency and the refractive index at a wavelength of 633 nm of the second resin layer when a transfer type photosensitive film is prepared. In addition, it is possible to improve developability while suppressing adsorption to the substrate.

[0094] Examples of the metal oxide particles include particles made of metal oxides such as zirconium oxide, titanium oxide, tin oxide, zinc oxide, indium tin oxide, indium oxide, aluminum oxide, yttrium oxide, etc. Among these, from the viewpoint of suppressing the bone visibility phenomenon, particles of zirconium oxide or titanium oxide are preferred.

[0095] When the transparent electrode material is ITO, it is preferable to use zirconium oxide nanoparticles as the zirconium oxide particles from the viewpoints of improving the refractive index and adhesion between the ITO and the transparent substrate. Among the zirconium oxide nanoparticles, those having a particle size distribution Dmax of 40 nm or less are preferable.

[0096] Zirconium oxide nanoparticles are commercially available as OZ-S30K (product name, manufactured by Nissan Chemical Industries, Ltd.), OZ-S40K-AC (product name, manufactured by Nissan Chemical Industries, Ltd.), SZR-K (zirconium oxide methyl ethyl ketone dispersion, manufactured by Sakai Chemical Industry Co., Ltd., product name), and SZR-M (zirconium oxide methanol dispersion, manufactured by Sakai Chemical Industry Co., Ltd., product name).

[0097] It is also possible to incorporate titanium oxide nanoparticles as component (E) in the second resin layer 30. Furthermore, among the titanium oxide nanoparticles, those having a particle size distribution Dmax of 50 nm or less are preferred, and 10 to 50 nm are more preferred.

[0098] In addition to the above-mentioned metal oxide particles, the component (E) may also be oxide particles or sulfide particles containing atoms such as Mg, Al, Si, Ca, Cr, Cu, Zn, Ba, etc. These may be used alone or in combination of two or more kinds.

[0099] In addition to the above metal oxide particles, it is also possible to use organic compounds such as compounds having a triazine ring, compounds having an isocyanuric acid skeleton, compounds having a fluorene skeleton, etc. This can improve the refractive index at a wavelength of 633 nm.

[0100] The thickness of the second resin layer 30 may be 0.01 to 1 μm, preferably 0.03 to 0.5 μm, more preferably 0.04 to 0.3 μm, further preferably 0.07 to 0.25 μm, and particularly preferably 0.05 to 0.2 μm. By having a thickness of 0.01 to 1 μm, it is possible to further reduce the reflected light intensity of the entire screen. In addition, it is preferable that the thickness of the second resin layer after curing is also within the above range.

[0101] When the second resin layer 30 is a single layer with a uniform thickness in the thickness direction, the refractive index of the second resin layer 30 can be determined as follows using ETA-TCM (product name, manufactured by AudioDevGmbH). The following measurement is performed under the condition of 25°C. (1) The coating liquid for forming the second resin layer is evenly coated onto a glass substrate having a thickness of 0.7 mm and an area of ​​10 cm length x 10 cm width using a spin coater, and then dried for 3 minutes in a hot air retention dryer at 100°C to remove the solvent, thereby forming a second resin layer. (2) Next, the sample is placed in a box dryer (manufactured by Mitsubishi Electric Corporation, model number: NV50-CA) heated to 140° C. for 30 minutes to obtain a sample for refractive index measurement having a second resin layer. (3) Next, the refractive index of the obtained sample for refractive index measurement is measured at a wavelength of 633 nm using ETA-TCM (product name, manufactured by AudioDevGmbH).

[0102] The refractive index of the first resin layer in a single layer can also be measured in the same manner. In the case of a transfer-type photosensitive film, since it is difficult to measure the refractive index of the second resin layer in a single layer, the refractive index is taken as the value of the outermost layer on the protective film side of the second resin layer.

[0103] (other layers) The transfer type photosensitive film of the present invention may have other layers appropriately selected within the scope of obtaining the effects of the present invention. The other layers are not particularly limited and can be appropriately selected according to the purpose, and examples thereof include a cushion layer, an oxygen shielding layer, a peeling layer, and an adhesive layer. The transfer type photosensitive film may have one of these layers alone, or may have two or more of them. It may also have two or more layers of the same type.

[0104] (Protective film) Examples of the protective film 40 include films of polyethylene, polypropylene, polyethylene terephthalate, polycarbonate, polyethylene-vinyl acetate copolymer, polyethylene-vinyl acetate copolymer, and laminated films of these films and polyethylene.

[0105] The thickness of the protective film 40 is preferably 5 to 100 μm, but from the viewpoint of storing the transfer type photosensitive film 1 in a roll form, it is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, and particularly preferably 40 μm or less.

[0106] The minimum value of the total light transmittance (Tt) in the visible light region of 400 to 700 nm wavelengths of the cured film portion (excluding the support film 10 and the protective film 40) obtained by curing the first resin layer 20 and the second resin layer 30 in the transfer type photosensitive film 1 is preferably 90.00% or more, more preferably 90.50% or more, and even more preferably 90.70% or more. If the total light transmittance in the general visible light wavelength region of 400 to 700 nm is 90.00% or more, when protecting a transparent electrode in the sensing region of a touch panel (touch sensor), it is possible to sufficiently suppress a decrease in image display quality, color tone, and brightness in the sensing region.

[0107] The first resin layer 20 and the second resin layer 30 of the transfer type photosensitive film 1 can be formed, for example, by preparing a coating liquid for forming the first resin layer and a coating liquid for forming the second resin layer, applying them to the support film 10 and the protective film 40, respectively, and drying them. The transfer type photosensitive film 1 can be formed by bonding the support film 10 on which the first resin layer 20 is formed and the protective film 40 on which the second resin layer 30 is formed, in a state in which the first resin layer 20 and the second resin layer 30 face each other. The transfer type photosensitive film 1 can also be formed by applying a coating liquid containing the coating liquid for forming the first resin layer on the support film 10 and drying it, and then applying the coating liquid for forming the second resin on the first resin layer 20 and drying it, and bonding the protective film 40.

[0108] The coating liquid can be obtained by uniformly dissolving or dispersing the photosensitive resin composition according to the embodiment described above and each component constituting the second resin layer in a solvent.

[0109] The solvent used as the coating liquid is not particularly limited, and a known solvent can be used.Specific examples of the solvent include acetone, methyl ethyl ketone, methyl isobutyl ketone, toluene, methanol, ethanol, propanol, butanol, methylene glycol, ethylene glycol, propylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol dimethyl ether, diethylene glycol ethyl methyl ether, diethylene glycol diethyl ether, propylene glycol monomethyl ether, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, chloroform, and methylene chloride.

[0110] Examples of the coating method include doctor blade coating, Mayer bar coating, roll coating, screen coating, spinner coating, inkjet coating, spray coating, dip coating, gravure coating, curtain coating, and die coating.

[0111] There are no particular limitations on the drying conditions, but the drying temperature is preferably 60 to 130° C., and the drying time is preferably 0.5 to 30 minutes.

[0112] [Method of forming a cured film pattern] FIG. 2 is a schematic cross-sectional view showing a laminate having a cured film formed on a substrate with a transparent electrode pattern using a transfer type photosensitive film according to one embodiment of the present invention. The laminate 100 shown in FIG. 2 includes a substrate 50 with a transparent electrode pattern having a transparent electrode pattern 50a, and a cured film 60 provided on the transparent electrode pattern 50a of the substrate 50 with a transparent electrode pattern. The cured film 60 is a cured film consisting of a cured first resin layer 22 and a cured second resin layer 32, and is formed using the transfer type photosensitive film 1 of this embodiment. The cured film 60 fulfills both the function of protecting the transparent electrode pattern 50a and the function of making the transparent electrode pattern 50a invisible or improving the visibility of the touch screen. Hereinafter, one embodiment of a method for producing a laminate in which a cured film is formed on a substrate with a transparent electrode pattern will be described.

[0113] -Lamination process- First, the protective film 40 of the transfer type photosensitive film 1 is removed, and then the second resin layer 30, the first resin layer 20, and the support film 10 are laminated (transferred) by pressure bonding from the second resin layer 30 side onto the surface of the substrate 50 with a transparent electrode pattern. An example of the pressure bonding means is a pressure bonding roll. The pressure bonding roll may be equipped with a heating means so that heat pressure bonding can be performed.

[0114] The heating temperature in the case of thermocompression bonding is preferably 10 to 160°C, more preferably 20 to 150°C, and even more preferably 30 to 150°C, from the viewpoint of adhesion between the second resin layer 30 and the substrate 50 with a transparent electrode pattern, and from the viewpoint of preventing the components of the first resin layer 20 or the second resin layer 30 from being thermally cured or thermally decomposed.

[0115] In addition, the pressure during the heat and pressure bonding is set to a linear pressure of 50 to 1×10 from the viewpoint of suppressing deformation of the substrate 50 with a transparent electrode pattern while sufficiently ensuring adhesion between the second resin layer 30 and the substrate 50 with a transparent electrode pattern. 5 N / m, and 2.5×10 2 ~5×10 4 N / m is more preferable, and 5×10 2 ~4×104 It is more preferable to set the axial length to N / m.

[0116] When the transfer type photosensitive film 1 is heat-pressed as described above, it is not always necessary to preheat the substrate 50 having a transparent electrode pattern, but the substrate 50 having a transparent electrode pattern may be preheated in order to further improve the adhesion between the second resin layer 30 and the substrate 50 having a transparent electrode pattern. The treatment temperature at this time is preferably 30 to 150°C.

[0117] (base material) Examples of the substrate constituting the substrate 50 having a transparent electrode pattern include substrates such as glass plates, plastic plates, and ceramic plates used in touch panels (touch sensors).

[0118] (Transparent electrodes and metal wiring) The transparent electrode can be formed by using a conductive metal oxide film such as ITO and IZO (Indium Zinc Oxide). The transparent electrode can also be formed by using a photosensitive film having a photocurable resin layer using conductive fibers such as silver fibers and carbon nanotubes. The metal wiring can be formed by using a conductive material such as Au, Ag, Cu, Al, Mo, C, etc., by a method such as screen printing or vapor deposition. An insulating layer or an index matching layer may be provided on the substrate between the substrate and the electrode. The index matching layer may have the same composition as the second resin layer 30 described above.

[0119] -Exposure process- Next, the predetermined parts of the first resin layer and the second resin layer after the transfer are irradiated with active light in a pattern through a photomask. When irradiating with active light, if the support film 10 on the first resin layer and the second resin layer is transparent, it can be irradiated with active light as it is, and if it is opaque, it is removed before irradiating with active light. As the light source of the active light, a known active light source can be used. In this specification, the pattern is not limited to the shape of the fine wiring that forms the circuit, but also includes a shape in which only the connection part with another substrate is removed in a rectangular shape and a shape in which only the frame part of the substrate is removed.

[0120] The exposure dose of actinic rays is 1×10 2 ~1×10 4 J / m 2 The irradiation may be accompanied by heating. The irradiation dose of this actinic ray is 1×10 2 J / m 2 If the amount is more than 1×10, the photocuring of the first resin layer and the second resin layer can be sufficiently promoted. 4 J / m 2 If the thickness is equal to or less than this, discoloration of the first resin layer and the second resin layer tends to be suppressed.

[0121] Next, the unexposed portions of the first resin layer and the second resin layer after the irradiation with the actinic rays are removed with a developer to form a cured film (refractive index adjusting pattern) 60 that covers a part or the whole of the transparent electrode. Note that, if a support film 10 is laminated on the first resin layer and the second resin layer after the irradiation with the actinic rays, it is removed, and then the development step is performed.

[0122] The development step can be carried out by known methods such as spraying, showering, rocking immersion, brushing, scrubbing, etc., using known developers such as an alkaline aqueous solution, an aqueous developer, an organic solvent, etc. Among them, spray development using an alkaline aqueous solution is preferred from the viewpoint of environment and safety. The development temperature and time can be adjusted within the conventionally known ranges.

[0123] In this embodiment, a cured film pattern was formed using a transfer type photosensitive film, but a cured film pattern can also be formed in a similar manner when a transfer type photosensitive film not having a second resin layer is used.

[0124] (cured film) The cured film according to the present invention may be a cured film obtained by curing the first resin layer and the second resin layer of the transfer photosensitive film of the present embodiment. For example, when most of the second resin layer is covered by the first resin layer and is not exposed, the second resin layer does not necessarily need to be cured. The cured film according to the present invention also includes such a case where the first resin layer is cured and the second resin layer is not cured. It is preferable that the cured film according to the present invention is formed in a pattern.

[0125] When the transfer type photosensitive film does not have a second resin layer, the cured film according to the present invention may be a cured film obtained by curing the first resin layer.

[0126] The transfer type photosensitive film according to the present embodiment can be applied to the formation of a protective film in various electronic components. The electronic components according to the present embodiment include a cured film pattern formed using the transfer type photosensitive film. Examples of the electronic components include touch sensors, touch panels, liquid crystal displays, organic electroluminescence, solar cell modules, printed wiring boards, and electronic paper.

[0127] For example, a touch sensor can include the laminate 100 shown in Figure 2. When the touch sensor is assembled into a module such as a touch panel, OCA can be used to bond the cover glass and the laminate 100.

[0128] Fig. 3 is a schematic top view showing a touch panel according to an embodiment of the present invention. Fig. 3 shows an example of a capacitive touch panel. The touch panel shown in Fig. 3 has a touch screen 102 for detecting touch position coordinates on one side of a transparent substrate 101, and transparent electrodes 103 and 104 for detecting capacitance changes in this area are provided on the transparent substrate 101.

[0129] The transparent electrodes 103 and 104 detect the X and Y coordinates of the touch position, respectively.

[0130] On the transparent base material 101, there is provided a lead-out wiring 105 for transmitting a detection signal of a touch position from the transparent electrodes 103 and 104 to an external circuit. Furthermore, the lead-out wiring 105 and the transparent electrodes 103 and 104 are connected by a connection electrode 106 provided on the transparent electrodes 103 and 104. Furthermore, a connection terminal 107 for connection to an external circuit is provided on an end of the lead-out wiring 105 opposite to the connection portion with the transparent electrodes 103 and 104.

[0131] As shown in FIG. 3, in the touch panel according to this embodiment, the transfer type photosensitive film of this embodiment is used to form a cured film pattern 123 across the area where the transparent electrode pattern is formed and the area where the transparent electrode pattern is not formed. The cured film pattern 123 is made of a cured first resin layer and a cured second resin layer. When a transfer type photosensitive film without a second resin layer is used, the cured film pattern 123 is made of a cured first resin layer. This cured film pattern 123 can simultaneously perform the function of protecting the transparent electrode 103, the transparent electrode 104, the lead wiring 105, the connection electrode 106, and the connection terminal 107, and the function of preventing the bone appearance phenomenon in the sensing area (touch screen) 102 formed from the transparent electrode pattern. In addition, by using the transfer type photosensitive film of this embodiment, the cured film pattern 123 can have a sufficiently small surface step. EXAMPLES

[0132] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0133] [Preparation of binder polymer solution] (Synthesis Example A1) 85.7 parts by mass of 1-methoxy-2-propanol (manufactured by Daicel Chemical Industries, Ltd.) was added to the reaction vessel in advance and heated to 80°C. On the other hand, 46 parts by mass of cyclohexyl methacrylate, 2 parts by mass of methyl methacrylate, 52 parts by mass of methacrylic acid, and 10 parts by mass of an azo-based polymerization initiator (manufactured by Wako Pure Chemical Industries, Ltd., V-601) were mixed to obtain a mixed solution. This mixed solution was dropped into the above reaction vessel at 80°C over a period of 2 hours under a nitrogen gas atmosphere. After dropping, the mixture was reacted for 4 hours to obtain an acrylic resin solution.

[0134] Next, 2.5 parts by mass of hydroquinone monomethyl ether and 8.4 parts by mass of tetraethylammonium bromide were added to the acrylic resin solution, and then 32 parts by mass of glycidyl methacrylate was dropped over 2 hours. After the dropwise addition, the mixture was reacted at 80° C. for 4 hours while blowing air into it, and then propylene glycol monomethyl ether acetate was added as a solvent so that the solid content concentration was 45% by mass, to obtain a binder polymer solution A1. The amounts of cyclohexyl methacrylate, methyl methacrylate, methacrylic acid, and glycidyl methacrylate were adjusted so that x:l:y:z=46 mol%:2 mol%:20 mol%:32 mol%.

[0135] (Synthesis example A2) A flask equipped with a stirrer, a reflux condenser, an inert gas inlet, and a thermometer was charged with 62 parts by mass of propylene glycol monomethyl ether and 62 parts by mass of toluene, and the temperature was raised to 80°C under a nitrogen gas atmosphere. While maintaining the reaction temperature at 80°C ± 2°C, the compounds shown in Table 1 and 1.5 parts by mass of 2,2'-azobis(isobutyronitrile) were uniformly added dropwise over 4 hours. After the addition, stirring was continued at 80°C ± 2°C for 6 hours to obtain a binder polymer solution A2 (solid content 45% by mass) having a weight average molecular weight of 30,000 and an acid value of 156.6 mgKOH / g.

[0136] [Table 1]

[0137] (Examples 1 to 13 and Comparative Examples 1 to 11) [Preparation of Coating Solution for Forming First Resin Layer] The components shown in Tables 2 and 3 were mixed in the amounts (unit: parts by mass) shown in the tables and mixed for 15 minutes using a stirrer to prepare a coating liquid for forming a first resin layer. In Tables 2 and 3, the amount of component (A) indicates the amount of solids. The coating liquid was adjusted to a solids content of 20 to 30 mass % using methyl ethyl ketone as a solvent.

[0138] [Preparation of Coating Liquid for Forming Second Resin Layer] The components shown in Table 3 were mixed in the amounts (unit: parts by mass) shown in the same table and mixed for 15 minutes using a stirrer to prepare a coating liquid for forming a second resin layer. In Table 3, the amount of component (A) indicates the amount of solid content.

[0139] [Table 2]

[0140] [Table 3]

[0141] [Table 4]

[0142] [Table 5]

[0143] The component symbols in Tables 2 to 5 have the following meanings. [Component (A)] A1: Binder polymer solution prepared by the method described above A2: Binder polymer solution prepared by the method described above

[0144] [(B) component] A-DCP: Tricyclodecane dimethanol diacrylate (product name, manufactured by Shin-Nakamura Chemical Co., Ltd.) DPHA: Dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical, product name "A-DPH")

[0145] [(C) component] TPO: 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (manufactured by BASF Ltd., product name "IRGACURE TPO") 819: Bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (BASF Ltd., product name "IRGACURE 819") OXE01: 1,2-Octanedione, 1-[4-(phenylthio)phenyl-, 2-(O-benzoyloxime)] (manufactured by BASF Ltd., product name "IRGACURE OXE 01") OXE02: Ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(0-acetyloxime) (manufactured by BASF Ltd., product name "IRGACURE OXE 02") 184: 1-Hydroxy-cyclohexyl-phenyl-ketone (BASF Ltd., product name "IRGACURE 184") 651: 2,2-dimethoxy-1,2-diphenylethan-1-one (BASF Ltd., product name "IRGACURE 651") 754: Mixture of oxyphenylacetic acid, 2-[2-oxo-2-phenylacetoxyethoxy]ethyl ester and oxyphenylacetic acid, 2-(2-hydroxyethoxy)ethyl ester (manufactured by BASF Ltd., product name "IRGACURE 754")

[0146] [(E) component] E1: Zirconium oxide nanoparticle dispersion (Nissan Chemical Industries, Ltd., product name "OZ-S30K")

[0147] [Preparation of transfer-type photosensitive film] (With second resin layer) A 30 μm thick polypropylene film (manufactured by Oji F-Tex Co., Ltd., product name: ES-201) was used as a protective film, and the coating liquid for forming the second resin layer prepared above was uniformly applied onto the protective film using a die coater. The coating liquid was then dried for 3 minutes in a hot air retention dryer at 110°C to remove the solvent, forming a second resin layer with a thickness of 60 nm and a refractive index of 1.4.

[0148] A 16 μm-thick polyethylene terephthalate film (manufactured by Toray Industries, Inc., product name: FB40) was used as a support film, and the coating liquid for forming the first resin layer prepared above was uniformly applied onto the support film using a comma coater, and the coating liquid was dried for 3 minutes in a hot air convection dryer at 110°C to remove the solvent, forming a first resin layer with a thickness of 8 μm.

[0149] Next, the protective film having the second resin layer and the support film having the first resin layer were bonded together at 23°C using a laminator (manufactured by Hitachi Chemical Co., Ltd., product name: HLM-3000 type) to produce a transfer-type photosensitive film in which the protective film, the second resin layer, the first resin layer and the support film were laminated in that order.

[0150] (When the second resin layer is not present) A 16 μm-thick polyethylene terephthalate film (manufactured by Toray Industries, Inc., product name: FB40) was used as a support film, and the coating liquid for forming the first resin layer prepared above was uniformly applied onto the support film using a comma coater, and the coating liquid was dried for 3 minutes in a hot air convection dryer at 110°C to remove the solvent, forming a first resin layer with a thickness of 8 μm.

[0151] Next, the support film having the obtained first resin layer was bonded to a 30 μm thick polypropylene film (manufactured by Oji F-Tex Co., Ltd., product name: ES-201) as a protective film at 23°C to produce a transfer-type photosensitive film in which the protective film, the first resin layer and the support film were laminated in that order.

[0152] [Step evaluation test] First, a test for evaluating the depression (step) on the cured film surface formed by the transfer type photosensitive film will be described with reference to Fig. 4. Note that Fig. 4 shows the case of evaluating a transfer type photosensitive film that does not have a second resin layer, but when evaluating a transfer type photosensitive film that has a second resin layer, the same applies except that the first resin layer 20 has a laminated structure of the first resin layer and the second resin layer.

[0153] A substrate 52 (ITO substrate) for evaluation was prepared. On this substrate 52, while peeling off the protective film of the transfer type photosensitive film obtained in the Examples and Comparative Examples, the first resin layer 20 or, in the case where the transfer type photosensitive film has a second resin layer, the second resin layer 30 was placed facing the substrate, and laminated under the conditions of 100° C., 0.6 m / min, and 0.4 MPa.

[0154] After lamination, the substrate was cooled, and when the temperature of the substrate reached 23° C., an exposure machine having a high-pressure mercury lamp (manufactured by Oak Manufacturing Co., Ltd., product name: EXM-1201) was used to expose the substrate from the support film 10 side to 50 mJ / cm 2 The film was irradiated with light through a mask 70 having a predetermined pattern at an exposure dose L1 (see FIG. 4(a)).

[0155] Next, the mask 70 is removed and 10 mJ / cm 2 The sample was irradiated with light at an exposure dose of L2 (see FIG. 4(b)).

[0156] Next, the support film 10 was removed, and 375 mJ / cm 2 The sample was irradiated with light at an exposure dose of L3 (see FIG. 4(c)).

[0157] Next, after annealing at 140 °C for 30 min, the total exposure dose was 435 mJ / cm 2 The surface S1 of the high reaction rate part, which is the surface with a total exposure of 385 mJ / cm 2The height difference G (nm) between the surface S2 of the low reaction rate portion and the surface S1 was measured (see FIG. 4(d)). The height difference G (nm) was measured using a laser microscope (manufactured by Lasertec Corporation).

[0158] If the step is 120 nm or less, the pattern visibility can be sufficiently suppressed. In addition, when forming the laminate 100 shown in FIG. 2, if the concave step on the cured film surface is 120 nm or less, the following effects are achieved. When forming a module such as a touch panel using the laminate 100, OCA is used to bond the cover glass and the laminate 100. Meanwhile, OCA is required to have adhesion reliability under high temperature and high humidity with respect to the cured film to which it adheres, but if there is a minute step on the cured film surface, the step may cause a problem that the OCA floats (peels off). If the step on the cured film surface is 120 nm or less, the occurrence of the above problem can be suppressed and the adhesion reliability of OCA under high temperature and high humidity can be improved.

[0159] [Evaluation of pattern visibility] The annealed sample obtained in the step evaluation test was fixed on a black board, exposed to light from an oblique angle, and visually observed, and evaluated according to the following criteria. ○: The pattern is not visible or is difficult to see. ×: Pattern is visible.

[0160] [Moisture permeability of cured film] Five transfer-type photosensitive films were prepared. First, the protective film of the first transfer-type photosensitive film was peeled off, and this was laminated on a filter paper (Advantec, No. 5C, φ90 mm circular, thickness 130 μm) under the conditions of a roll temperature of 100 ° C., a substrate feed rate of 0.6 m / min, and a pressure (cylinder pressure) of 0.5 MPa. Next, the support film was peeled off, and the second transfer-type photosensitive film was peeled off and laminated on the first resin layer laminated on the filter paper. By repeating this operation, a laminate in which a first resin layer (i.e., five first resin layers) having a thickness of 40 μm and a support film were laminated on the filter paper was produced.

[0161] In addition, when the transfer-type photosensitive film had a second resin layer, a laminate was prepared in the same manner as above, in which five layers of the first resin layer and the second resin layer, each about 40 μm thick, and a support film were laminated on filter paper.

[0162] The laminate was exposed to light perpendicular to the support film surface using a parallel light exposure machine (EXM1201, manufactured by Oak Manufacturing Co., Ltd.) at a dose of 0.6 J / m 2 UV light was irradiated.

[0163] Next, the support film of the laminate irradiated with ultraviolet light was peeled off and removed, and the laminate was exposed to light from vertically above with an exposure dose of 1×10 4 J / m 2 In this way, a sample for moisture permeability measurement in the form of a cured film formed on the filter paper was obtained.

[0164] Next, moisture permeability was measured with reference to JIS standard (Z0208, cup method). First, moisture absorbent (20 g of calcium chloride (anhydrous)) was placed in a measuring cup (φ60 mm, depth 15 mm, Muraimoto Manufacturing Co., Ltd.). Next, a circular sample piece with a diameter of 70 mm was cut with scissors from the moisture permeability measurement sample and used to cover the measuring cup. The sample was left for 24 hours under conditions of 40°C and 90% RH in a constant temperature and humidity chamber. The moisture permeability was calculated from the change in the total mass of the measuring cup, moisture absorbent, and circular sample piece before and after leaving the sample. If the moisture permeability was 200 g / m 2 If it is less than 24 hours, the rust prevention is good. [Explanation of symbols]

[0165] 1...transfer type photosensitive film, 10...support film, 20...first resin layer, 22...cured first resin layer, 30...second resin layer, 32...cured second resin layer, 40...protective film, 50...substrate with transparent electrode pattern, 50a...transparent electrode pattern, 60...cured film, 100...laminated body, 101...transparent substrate, 102...sensing area, 103, 104...transparent electrodes, 105...drawing wiring, 106...connecting electrode, 107...connecting terminal, 123...cured film pattern.

Claims

1. A support film and a first resin layer provided on the support film (excluding the first resin layer containing a silica filler having an average particle size of 300 nm or less), the first resin layer is formed from a photosensitive resin composition containing a binder polymer, a photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton, and an acylphosphine oxide-based photopolymerization initiator (excluding a photosensitive resin composition in which at least one of the binder polymer and the photopolymerizable compound contains a urethane bond, and a photosensitive resin composition containing an organosiloxane compound having a cyclic siloxane skeleton of six or more members, and in which the organosiloxane compound having a cyclic siloxane skeleton of six or more members has a skeleton represented by the following general formula (1)), the binder polymer is a copolymer containing structural units derived from (meth)acrylic acid and an alkyl (meth)acrylate ester, and contains an alicyclic hydrocarbon group having 5 to 20 carbon atoms in a side chain, a group having an acidic group in a side chain, and a group having a (meth)acryloyl group in a side chain; a photosensitive transfer film used for forming a cured film pattern on an electrode pattern, the photopolymerizable compound being present in an amount of 20 parts by mass or more relative to 100 parts by mass of the total amount of the binder polymer and the photopolymerizable compound; 【Chemistry 1】 (In the formula, n represents an integer of 1 or more.)

2. 2. The transfer type photosensitive film according to claim 1, wherein the acylphosphine oxide photopolymerization initiator comprises 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide.

3. 3. The transfer type photosensitive film according to claim 1, wherein the photosensitive resin composition of the first resin layer further contains an oxime ester-based photopolymerization initiator.

4. The transfer type photosensitive film according to any one of claims 1 to 3, further comprising a second resin layer containing metal oxide particles provided on the first resin layer.

5. The transfer type photosensitive film according to claim 4 , wherein the second resin layer contains a photopolymerizable compound having a tricyclodecane skeleton or a tricyclodecene skeleton.

6. The transfer type photosensitive film according to any one of claims 1 to 5, which is used for forming a cured film on a substrate having an ITO electrode pattern and an index matching layer.

7. A step of laminating the first resin layer of the transfer type photosensitive film according to any one of claims 1 to 3 onto a substrate having an electrode pattern such that the side of the substrate on which the electrode pattern is provided and the first resin layer are in close contact with each other; a step of exposing a predetermined portion of the first resin layer on the base material to light, and then removing other than the predetermined portion to form a cured film pattern that covers a part or all of the electrode pattern; A method for forming a cured film pattern comprising the steps of:

8. a step of laminating the second resin layer and the first resin layer of the transfer type photosensitive film according to claim 4 or 5 onto a substrate having an electrode pattern such that the side of the substrate on which the electrode pattern is provided is in close contact with the second resin layer; a step of exposing predetermined portions of the second resin layer and the first resin layer on the base material to light, and then removing portions other than the predetermined portions to form a cured film pattern that covers a part or all of the electrode pattern; A method for forming a cured film pattern comprising the steps of:

9. A cured film obtained by curing the first resin layer in the transfer type photosensitive film according to any one of claims 1 to 3.

10. A cured film obtained by curing only the first resin layer, or both the first resin layer and the second resin layer, of the transfer type photosensitive film according to claim 4 or 5.

11. A touch panel comprising a cured film pattern consisting of a cured film of the first resin layer in the transfer type photosensitive film according to any one of claims 1 to 3, or a cured film of the second resin layer and a cured film of the first resin layer in the transfer type photosensitive film according to claim 4 or 5.

Citation Information

Patent Citations

  • Portable sprayer

    JP1979058215A

  • Change-gear controller of induction motor

    JP1985082083A

  • Resin substrate for liqud crystal display

    JP1996240800A

  • Photosensitive composition, photosensitive resin transfer film, manufacturing method of photo spacer, substrate for liquid crystal display device, and liquid crystal display device

    JP2008146018A

  • Photosensitive composition, photosensitive-resin transfer film, resin pattern, method for manufacturing resin pattern, base board for liquid crystal display, and liquid crystal display

    JP2010237589A